Obinutuzumab and ibrutinib induction therapy followed by a minimal residual disease-driven strategy in patients with chronic lymphocytic leukaemia (ICLL07 FILO): a single-arm, multicentre, phase 2 trial. Issue 9 (September 2019) - Michallet, Anne-Sophie; Dilhuydy, Marie-Sarah; Subtil, Fabien; Rouille, Valerie; Mahe, Beatrice; Laribi, Kamel; Villemagne, Bruno; Salles, Gilles; Tournilhac, Olivier; Delmer, Alain; Portois, Christelle; Pegourie, Brigitte; et al.
Summary: Background: In patients with chronic lymphocytic leukaemia, achievement of a complete response with minimal residual disease of less than 0·01% (ie, <1 chronic lymphocytic leukaemia cell per 10 000 leukocytes) in bone marrow has been associated with improved progression-free survival. We aimed to explore the activity of induction therapy for 9 months with obinutuzumab and ibrutinib, followed up with a minimal residual disease-driven therapeutic strategy for 6 additional months, in previously untreated patients. Methods: We did a single-arm, phase 2 trial in 27 university hospitals, general hospitals, and specialist cancer centres in France. Eligible patients were at least 18 years old and previously untreated, and had immunophenotypically confirmed B-cell chronic lymphocytic leukaemia; an Eastern Cooperative Oncology Group (ECOG) performance status score of less than 2; a Binet stage C according to IWCLL 2008 criteria or Binet stage A and B with active disease; no 17p deletion or absence of p53 mutation; and were considered medically fit. In the first part of the study (induction phase), all participants received eight intravenous infusions of obinutuzumab 1000 mg over six 4-weekly cycles and oral ibrutinib 420 mg once per day for 9 months. In part 2, after assessment on day 1 of month 9, patients with a complete response and bone marrow minimal residual disease of less than 0·01% received only oral ibrutinib 420 mg once per day for 6 additional months. Patients with a partial response, or with a complete response and bone marrow minimal residual disease of 0·01% or more, received 6 months of four 4-weekly cycles of intravenous fludarabine, cyclophosphamide, and obinutuzumab 1000 mg, alongside continuing ibrutinib 420 mg once per day. The primary endpoint was the proportion of patients achieving a complete response with bone marrow minimal residual disease less than 0·01% on day 1 of month 16 assessed by intention to treat (ITT). This trial is registered withClinicalTrials.gov (numberNCT02666898 ) and is still open for follow-up. Findings: Between Oct 27, 2015, and May 16, 2017, 135 patients were enrolled. After induction treatment (day 1 of month 9), 130 patients were evaluable, of which ten (8%) achieved a complete response with bone marrow minimal residual disease of less than 0·01% and were assigned to ibrutinib, and 120 (92%) were assigned to ibrutinib plus fludarabine, cyclophosphamide, and obinutuzumab. After minimal residual disease-guided treatment (day 1 of month 16), 84 (62%, 90% CI 55–69) of 135 patients (ITT population) achieved a complete response with bone marrow minimal residual disease of less than 0·01%. The most common haematological adverse event was thrombocytopenia (in 45 [34%] of 133 patients at grade 1–2 in months 1–9 and in 43 [33%] of 130 patients at grade 1–2 in months 9–15). The most common non-haematological adverse events were infusion-related reactions (in 83 [62%] patients at grade 1–2 in months 1–9) and gastrointestinal disorders (in 62 [48%] patients at grades 1 and 2 in months 9–15). 49 serious adverse events occurred, most frequently infections (ten), cardiac events (eight), and haematological events (eight). No treatment-related deaths occurred. Interpretation: Obinutuzumab and ibrutinib induction therapy followed by a minimal residual disease driven strategy is safe and active in patients with previously untreated chronic lymphocytic leukaemia. With longer follow-up, including assessing the evolution of minimal residual disease, if response is maintained, this strategy could be an option in the first-line setting in patients with chronic lymphocytic leukaemia, although randomised evidence is needed. Funding: Roche, Janssen.